Implementasi Metode Design Thinking Dalam Perancangan dan Pembuatan Aplikasi Primer Koperasi - Wilyanto martin Pandapotan Siregar; Sahyunan Harahap; Rio Septian Hardinata (Bulletin of Information Technology (BIT), 2024)
− A cooperative is a business entity consisting of individuals or cooperative legal entities that bases its activities on cooperative principles as a people's economic movement based on the principle of kinship. Primkop Kosek I Medan focuses on selling basic necessities and other materials to cooperative members through minimarket sales called Airforce Mart Kosek I Medan. Primkop Kosek I Medan's operational handling still uses book recording and recording on office computer applications such as Microsoft Excel. This causes problems such as inaccurate data recording and requiring a long time to search for data. The aim of this research is to design and build an application to help process data at Primkop Airforce Mart Kosek I Medan using the Design Thinking method. This application prototype was successfully implemented well where users easily operated the application and were able to manage goods and sales data at Airforce Mart Kosek I Medan so that users could more easily obtain sales results data and goods inventory data.